Identification of Annexin A1 interacting proteins in chronic myeloid leukemia KCL22 cells. Issue 16 (16th July 2013) - Colavita, Irene; Esposito, Nicola; Quintarelli, Concetta; Nigro, Ersilia; Pane, Fabrizio; Ruoppolo, Margherita; Salvatore, Francesco
<x xml:space="preserve">Abstract</x> In the present study, we used a functional proteomic approach to identify Annexin A1 (Anxa1) interacting proteins in the Philadelphia‐positive KCL22 cell line. We focused on Anxa1 because it is one of the major proteins upregulated in imatinib‐sensitive KCL22S cells versus imatinib‐resistant KCL22R. Our proteomic strategy revealed 21 interactors. Bioinformatic analysis showed that most of these proteins are involved in cell death processes. Among the proteins identified, we studied the interaction of Anxa1 with two phosphatases, Shp1 and Shp2, which were recently identified as biomarkers of imatinib sensitivity in patients affected by chronic myeloid leukemia. Our data open new perspectives in the search for annexin‐mediated signaling pathways and may shed light on mechanisms of resistance to imatinib that are unrelated to Bcr‐Abl activity. All mass spectrometry data have been deposited in the ProteomeXchange with identifier PXD000030.